Bioconversion of Plant Hydrolysate Biomass into Biofuels Using an Engineered Bacillus subtilis and Escherichia coli Mixed-whole Cell Biotransformation - Kim, Seo Yeong; Yang, Yung Hun; Choi, Kwon Young (Biotechnology and Bioprocess Engineering, 2020)
Bioconversion of organic biomass such as plant hydrolysate and organic waste into valuable biochemicals is very challenging. In this study, carbohydrate-rich watermelon rinds and protein-rich okara (soybean waste) were converted into biofuels of ethanol, isobutanol, and methylbutanols using an engineered Escherichia coli and Bacillus subtilis mixed-whole cell biotransformation. The engineered E. coli expressed the genes alsS, kivD, ilvC, ilvD, and yqhD, and the engineered B. subtilis expressed the genes leuDH, kivD, and yqhD. The growth inhibition of the B. subtilis strain, which was reduced by 50% with addition of 1 mM furfural, was restored by the addition of 1 g/mL of activated carbon. The ratio of the E. coil and B. subtilis was optimized depending on carbohydrate and protein composition of the hydrolysate. When the carbohydrate levels were high, a 4:1 ratio of engineered E. coli to B. subtilis led to the highest overall biofuel (1.1 g/L) and isobutanol (80%) production. Viability analysis of the engineered E. coli to B. subtilis strains showed that the E. coli strain had higher activity at the beginning of the biotransformation period, while the B. subtilis strain exhibited higher activity in the later stages. The results of the present study provide important information for future biochemical production research, particularly regarding the diversification of organic waste resources.
Keywords: Bacillus Subtilis; Engineered escherichia coli; Growth inhibition; Organic wastes; Production research; Protein composition; Watermelon rinds; Whole-cell biotransformations; Bacillus subtilis- Escherichia coli mixed biotransformation; biofuels; organic waste conversion; plant hydrolysate biomass